2020
DOI: 10.1007/jhep12(2020)158
|View full text |Cite
|
Sign up to set email alerts
|

All-plus helicity off-shell gauge invariant multigluon amplitudes at one loop

Abstract: We calculate one loop scattering amplitudes for arbitrary number of positive helicity on-shell gluons and one off-shell gluon treated within the quasi-multi Regge kinematics. The result is fully gauge invariant and possesses the correct on-shell limit. Our method is based on embedding the off-shell process, together with contributions needed to retain gauge invariance, in a bigger fully on-shell process with auxiliary quark or gluon line.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…the limit | | → 0. In this limit, we expect our off-shell amplitude to express as a sum of two on-shell amplitude where the off-shell gluon tends to an on-shell one with either positive or negative helicity (see justification in [9,10]). More explicitly :…”
Section: Validating the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the limit | | → 0. In this limit, we expect our off-shell amplitude to express as a sum of two on-shell amplitude where the off-shell gluon tends to an on-shell one with either positive or negative helicity (see justification in [9,10]). More explicitly :…”
Section: Validating the Resultsmentioning
confidence: 99%
“…So we already have the contribution from the amplitude with negative helicity gluon (the first term in the expression above). It can be demonstrated that the second term actually correspond to the amplitude with positive helicity gluon (but this is much less trivial, see the demonstration in [9]) . For = 3, we also verified that our result was in agreement with Lipatov's high energy effective action calculations (comparing it with results presented in [11]).…”
Section: Validating the Resultsmentioning
confidence: 99%
“…As mentioned in the introduction, the tree-level squared matrix element with the space-like initial-state gluon can be defined with the auxiliary parton method proposed in [73] and most recently applied in [82]. Let the desired parton-level process be…”
Section: The Auxiliary Parton Methodsmentioning
confidence: 99%
“…While a related study has been already presented in [18] within the Color-Glass-Condensate approach, we will investigate this problem within the context of Lipatov's high energy effective action [32,33]. Starting with [34][35][36][37][38] the systematic determination of perturbative higher order corrections has been worked out for this framework, while in [39] equivalence with the Color-Glass-Condensate formalism has been demonstrated, including an re-derivation of the Balitsky-JIMWLK evolution, see also [40,41] for reviews; for further recent studies based on this framework see also [42][43][44][45][46][47][48][49]. In [50] a systematic framework for the determination of next-to-leading order corrections at cross-section level has been worked out.…”
Section: Introductionmentioning
confidence: 99%